SlbHLH22-Induced Hypertrophy Development Is Related to the Salt Stress Response of the GTgamma Gene in Tomatoes - Baolu Cui; Min Yu; Jiaojiao Bai; Zhiguo Zhu (Metabolites, 2023)
Hypertrophy development induced by the overexpression of SlbHLH22 (also called SlUPA-like) was susceptible to Xanthomonas in tomatoes. Transcriptome and metabolome analyses were performed on the hypertrophy leaves of a SlbHLH22-overexpressed line (OE) and wild type (WT) to investigate the molecular mechanism. Metabolome analysis revealed that six key metabolites were over-accumulated in the OE, including Acetylserine/O-Acetyl-L-serine, Glucono-1,5-lactone, Gluconate, 2-Oxoglutarate, and Loganate, implying that the OE plants increased salt or oxidant resistance under normal growth conditions. The RNA-seq analysis showed the changed expressions of downstream genes involved in high-energy consumption, photosynthesis, and transcription regulation in OE lines, and we hypothesized that these biological processes were related to the GTgamma subfamily of trihelix factors. The RT-PCR results showed that the expressions of the GTgamma genes in tomatoes, i.e., SlGT-7 and SlGT-36, were suppressed in the hypertrophy development. The expression of the GTgamma gene was downregulated by salinity, indicating a coordinated role of GTgamma in hypertrophy development and salt stress. Further research showed that both SlGT-7 and SlGT-36 were highly expressed in leaves and could be significantly induced by abscisic acid (ABA). The GTgamma protein had a putative phosphorylation site at S96. These results suggested GTgamma’s role in hypertrophy development by increasing the salt resistance.